The Influence of E-Servqual and E-Trust on E-Loyalty : The Role of E-Satisfaction as an Intervening on Islamic Mobile Banking Customer - Haza Fatikah, Berliana; Albanna, Hasan (UIN Sunan Kalijaga Yogyakarta, 2022)
Research Aims: This study aims to analyze the effect of e-trust and e-service quality on loyalty through e-satisfaction of Islamic mobile banking users. The purpose of this study is to investigate the impact of trust and service quality on consumer loyalty through consumer satisfaction in the context of mobile banking. Design/methodology/approach: The sampling method used in this study was nonprobability sampling with a purposive sampling technique. The data was collected from 151 respondents who met the assessment criteria and were supposed to use mobile banking at least twice. This study used Structural Equation Model (SEM) analysis techniques, which were estimated by SmartPLS 3.0. Research Findings: The results show that e-service quality and e-trust have a positive effect on e-satisfaction; e-trust and e-satisfaction have a positive effect on e-loyalty; e-service quality does not affect e-loyalty; e-satisfaction can mediate the relationship between e-service quality and e-trust to e-loyalty; age and gender cannot moderate the relationship between e-satisfaction and e-loyalty Keywords: e-trust, e-service quality, e-satisfaction, e-loyalty, age, gender, Islamic mobile banking